2021
DOI: 10.21203/rs.3.rs-882567/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association between glycemic control and risk of venous thromboembolism in diabetic patients: A nested case-control study

Abstract: Background:Previous studies suggested an elevated risk of venous thromboembolism (VTE) among patients with type 2 diabetes mellitus (T2DM), with a possible sex difference. The impact of glycemic control on the risk of VTE is unclear. Our objective was to analyze the association between glycemic control and the risk of unprovoked (idiopathic) VTE in men and women with T2DM.Methods:We conducted a nested case-control analysis (1:4 matching) within a cohort of patients with incident T2DM between 1995–2019 using da… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…A meta-analysis revealed that the risk of VTE in diabetic patients was 1.4 times higher than that in nondiabetic individuals [29] , which is consistent with our ndings.One mechanism for the complication of thrombosis in diabetes may be the hyperglycaemia-induced production of excess superoxide in the mitochondrial electron transport chain, which activates several damage pathways [30] . Other studies [31,32] have also found that acute changes in glycaemia and insulin resistance in diabetic patients can exacerbate the hypercoagulable state, which in turn increases the risk of VTE.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis revealed that the risk of VTE in diabetic patients was 1.4 times higher than that in nondiabetic individuals [29] , which is consistent with our ndings.One mechanism for the complication of thrombosis in diabetes may be the hyperglycaemia-induced production of excess superoxide in the mitochondrial electron transport chain, which activates several damage pathways [30] . Other studies [31,32] have also found that acute changes in glycaemia and insulin resistance in diabetic patients can exacerbate the hypercoagulable state, which in turn increases the risk of VTE.…”
Section: Discussionmentioning
confidence: 99%